Feedbacks between hydrological processes in tropical South America and large-scale ocean-atmospheric phenomena (1997)
The hydroclimatology of tropical South America is strongly coupled to low-frequency large-scale oceanic and atmospheric phenomena occurring over the Pacific and the Atlantic Oceans. In particular, El Nin˜o–Southern Oscillation (ENSO) affects climatic and hydrologic conditions on timescales ranging from seasons to decades. With some regional differences in timing and amplitude, tropical South America exhibits negative rainfall and streamflow anomalies in association with the low–warm phase of the Southern Oscillation (El Nin˜o), and positive anomalies with the high–cold phase. Such dependence is illustrated in the hydroclimatology of Colombia through several empirical analyses: correlation, empirical orthogonal functions, principal component, and spectral analysis, and discussion of the major physical mechanisms. Observations show that ENSO’s effect on river discharges occurs progressively later for rivers toward the east in Colombia and northern South America. Also, the impacts of La Nin˜a are more pronounced than those of El Nin˜o. Evidence is also presented to show that processes arising from land–atmosphere interactions in tropical South America affect sea surface temperatures in the Caribbean and the north tropical Atlantic. A hypothesis is formulated to explain these feedback mechanisms through perturbations in precipitation, soil moisture, and evapotranspiration over the continent. To begin with, the occurrence of both phases of ENSO affects all those fields. The proposed mechanisms would constitute the ‘‘land– atmosphere’’ bridge connecting Pacific and Atlantic SST anomalies.